2019
DOI: 10.12659/msmbr.913436
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Oncosis/Necroptosis Are Enhanced in Cardiomyocytes from Heart Failure Patients

Abstract: BackgroundAlthough originally described as a survival mechanism, it is unknown whether and to what extent autophagy is implicated in the terminal stages of heart failure. Here, we studied magnitude and evolution of autophagy in patients with intractable heart failure.Material/MethodsMyocardial samples were obtained from 22 patients with ischemic cardiomyopathy and idiopathic dilated cardiomyopathy who were undergoing cardiac transplantation. Hearts from 11 patients who died from non-cardiac causes were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 40 publications
4
52
2
Order By: Relevance
“…Lipid exposure has been shown to cause cardiomyocyte apoptosis in vitro [139]; however, current studies show conflicting evidence in vivo [140][141][142]. Recent evidence has suggested that cardiomyocyte autophagy and necroptosis (a controlled form of necrosis) play a larger role than apoptosis [143]. Interestingly, even low levels of cardiomyocyte apoptosis induce HFrEF in animal models [144].…”
Section: Cardiomyocyte Cell Death: a Typical Characteristic Of Hfrefmentioning
confidence: 99%
“…Lipid exposure has been shown to cause cardiomyocyte apoptosis in vitro [139]; however, current studies show conflicting evidence in vivo [140][141][142]. Recent evidence has suggested that cardiomyocyte autophagy and necroptosis (a controlled form of necrosis) play a larger role than apoptosis [143]. Interestingly, even low levels of cardiomyocyte apoptosis induce HFrEF in animal models [144].…”
Section: Cardiomyocyte Cell Death: a Typical Characteristic Of Hfrefmentioning
confidence: 99%
“…In recent years, knowledge on necroptosis has advanced and a practically unknown process has become a well-established pathophysiological factor contributing to myocardial damage in various types of HF [ 4 , 7 , 9 , 10 , 30 ]. In our previous study, we have shown the activation of canonical necroptosis signaling being implicated in both infarcted and non-infarcted LV areas of failing rat hearts, while its execution mechanisms were restricted to the former area only.…”
Section: Discussionmentioning
confidence: 99%
“…Such activation of necroptotic signaling has been suggested to be associated with myocardial fibrosis, ventricular remodeling, inflammation and severe contractile dysfunction [ 8 ]. Likewise, studies employing explanted human failing hearts of various etiologies have shown the participation of necroptosis in HF-associated myocardial deterioration [ 4 , 7 ]. Some of these studies have also investigated autophagy and reported contradictory data on necroptosis-autophagy link in the heart [ 4 , 7 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations